2014
DOI: 10.1007/s13233-014-2172-0
|View full text |Cite
|
Sign up to set email alerts
|

pH-sensitive hydrogels based on (meth)acrylates and itaconic acid

Abstract: Novel hydrogels based on 2-hydroxyethyl methacrylate (HEMA), itaconic acid (IA) and different poly (alkylene glycol) (meth)acrylates (PAGM) (P(HEMA/IA/PAGM)) were synthesized. We investigated the influence of different PAGM components, with acrylic or methacrylic acid residues in the main chain and ethylene glycol (EG) and/or propylene glycol (PG) units in pendant chains of varying length, on the nature and inherent properties of P(HEMA/IA/PAGM) copolymeric hydrogels. Swelling studies revealed pH sensitive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…The FTIR spectra of PHEMA, PHEMA/A/GO, and PHEMA/G/GO samples are shown in Figure 1 . The PHEMA spectrum showed: O–H stretching vibration at approximately 3431 cm −1 , strong C=O vibration at 1716 cm −1 and C–H stretching vibrations at 2929 cm −1 and 2885 cm −1 [ 29 ]. FT-IR spectra of the PHEMA/A/GO and PHEMA/G/GO materials exhibited above listed PHEMA signals, gelatin (N–H stretching vibration around 3354 cm −1 , C–H stretching at 3003 cm −1 , C=O stretching at 1701 cm −1 for amide I, N–H definition at 1630 cm −1 for the amide II ) and alginate (1278 cm −1 C–O stretching, 1160 cm −1 C–C stretching, 1017 cm −1 C–O–C stretching) vibrations and the type and ratio of the component influenced on the intensity of the peaks [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of PHEMA, PHEMA/A/GO, and PHEMA/G/GO samples are shown in Figure 1 . The PHEMA spectrum showed: O–H stretching vibration at approximately 3431 cm −1 , strong C=O vibration at 1716 cm −1 and C–H stretching vibrations at 2929 cm −1 and 2885 cm −1 [ 29 ]. FT-IR spectra of the PHEMA/A/GO and PHEMA/G/GO materials exhibited above listed PHEMA signals, gelatin (N–H stretching vibration around 3354 cm −1 , C–H stretching at 3003 cm −1 , C=O stretching at 1701 cm −1 for amide I, N–H definition at 1630 cm −1 for the amide II ) and alginate (1278 cm −1 C–O stretching, 1160 cm −1 C–C stretching, 1017 cm −1 C–O–C stretching) vibrations and the type and ratio of the component influenced on the intensity of the peaks [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acrylate-based polymers tend to swell with an increase in pH, which tends to accelerate the release of a loaded AI. 25 , 26 The effects that soil characteristics have on release kinetics and formulation durability certainly require further systematic study considering a larger number of soil types.…”
Section: Resultsmentioning
confidence: 99%
“…The faster release rate measured in the sand could not be explained by differences in the soil pH value (5.2 and 7.2 for the sand and loam, respectively). Acrylate-based polymers tend to swell with an increase in pH, which tends to accelerate the release of a loaded AI. , The effects that soil characteristics have on release kinetics and formulation durability certainly require further systematic study considering a larger number of soil types.…”
Section: Resultsmentioning
confidence: 99%
“…Tomi c et al reported the in vitro release of Cephalexin in PBS (pH ¼ 7.4) at 37 C from the 2-hydroxyethyl methacrylate, itaconic acid and poly (alkylene glycol) methacrylates based hydrogel. The hydrogel releases less than 80% of drug within 10 h and ~100% release after 90 h [16]. Further, steady release of drug is observed after the initial burst release.…”
Section: Loading and In Vitro Release Of Cephalexinmentioning
confidence: 93%
“…Limited studies of release of Cephalexin by hydrogels are being reported in the literature. The Cephalexin delivery of hydrogel formed by 2-hydroxyethyl methacrylate, itaconic acid and poly (alkylene glycol) methacrylates is reported by Tomi c et al [16]. Barkhordari and Yadollahi reported enhanced protection and controlled liberation of Cephalexin drug in gastrointestinal tract using CMC encapsulated layered double hydroxides-drug nanohybrids [14].…”
Section: Introductionmentioning
confidence: 93%